The process of Ezra and Nehemiah- The process of displacing of the Jews of Iraq. - عدنان حسين عبد الستار (lark, 2019)
Abstract: The research is an attempt to answer the question of how the Jews of Iraq were displaced in the early of 1950s? the condition and the circumstances of the immigration of the Jews of Iraq , the mechanism of the immigration under the so – called " Ezra and Nehemiah process" a process that has been successful in practice , with the help of superpowers such as Britain and united states which pressed the Iraqi government at the time and forced it to bow and comply with them , As well as the secret movements and Zionist organization that have helped tremendously to open the door of immigration to the Jews , and spreading rumors and propaganda within the Jewish community as well as bombings that led in one way or another to push the Jews to leave .